Penerapan Algoritma MOORA dalam Menentukan Sekolah Dasar Terbaik - Athif Fauzan; Supriatin (The Indonesian Journal of Computer Science, 2022)
Elementary school is the first level of education for students who have an important role in the development of behavior, skills and talents. Thus, the selection of the best primary school becomes something important for parents, because this will affect the future of their children in the future. In this regard, parents are faced with many choices of primary schools, especially in the Purworejo area for their children. This study aims to assist parents in determining the best primary school that is right for their children by using a Decision Support System. The method used in this research is MOORA. Multi Objective Optimization On The Basic Of Ratio Analysis (MOORA) is a method that can filter the best alternatives because this method is able to determine goals based on conflicting criteria on several constraints, so the use of this method is very appropriate to solve existing problems. This study uses 6 criteria that have been determined as a form of reference in determining the best elementary school, namely Accreditation, School Location, School Facilities, School Achievement, Professional HR (Teachers), and Number of Excellent Programs. There are 7 elementary schools that will be used as alternative data, all of which are taken from elementary schools in Purworejo. Of the 7 elementary schools taken, 3 elementary schools with school codes SK03 = 0.3382 , SK01 = 0.2922 , and SK02 = 0.2538 were selected to be the best elementary schools in 2022.